How to Operationalize Inequality Issues in Country Work. (Policy Papers; Policy Paper, 2018)
Economic inclusion is the broad sharing of the benefits of, and the opportunities to participate in, economic growth. It embodies equitable outcomes related to financial well-being as well as opportunities in access to markets and resources, and protects the vulnerable. Economic inclusion is a high priority issue for the IMF. High inequality is negatively associated with macroeconomic stability and sustainable growth-core to the Fund's mandate in promoting systemic, balance of payments, and domestic stability. Some macroeconomic policies and reforms may have adverse distributional implications, which in turn can undermine public support for reforms. And, interest in distributional issues and inequality has grown among the membership, increasing the demand for the Fund to work in these areas. While the IMF has long recognized the importance of inequality issues, it has adopted in the recent years a more systematic and structured approach. In this regard, a pilot initiative on inequality was launched in 2015, with the third wave of countries currently participating. Once this wave is concluded, staff proposes to incorporate the analysis of inequality-related issues into broader country work where relevant. This note provides an overview of good practices and resources available to staff. The note is consistent with the 2015 Guidance Note for Surveillance Under Article IV Consultations and draws also on the 2013 Guidance Note on Jobs and Growth Issues in Surveillance and Program Work. It provides examples of good practices with respect to coverage of inequality-related issues in country reports and lays out the resources available to country teams, both with respect to existing analytical work as well as the availability of data and tools. Coverage of inequality issues in staff reports should be selective and calibrated to the degree of macroeconomic significance. All teams should consider whether inequality issues are relevant, taking into account also the authorities' priorities, but with no presumption that inequality will be covered everywhere or every year and in-depth coverage anticipated in only a limited number of cases any year. Staff should point to macroeconomic significance where it exists, with analysis focused on aspects with economic implications and specific policy advice limited to areas where there is Fund expertise.